2021
DOI: 10.1001/jamanetworkopen.2021.32209
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Nontechnical Skills During Robotic-Assisted Surgery Using Sensor-Based Communication and Proximity Metrics

Abstract: Nontechnical skills (NTS) include cognitive and interpersonal (eg, teamwork) skills 1 ; they are linked to patient outcomes in surgery. 2,3 Currently, NTS assessment in surgery relies on behavior ratings that are subjective, potentially biasing assessments, and requires trained raters, a limited resource.This study demonstrates a sensing-based system for objectively measuring intraoperative NTS. We hypothesized that objective, sensor-derived communication and proximity metrics are associated with NTS scores as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Participant NTS was evaluated using three metrics: Non- Technical Skills for Surgeons (NOTSS) score, leadership score (subject-matter evaluation on if necessary and appropriate leadership skill were displayed), and communication-based metrics. The communication metrics were used to decompose speech into key elements further discussed in Cha et al 2021.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participant NTS was evaluated using three metrics: Non- Technical Skills for Surgeons (NOTSS) score, leadership score (subject-matter evaluation on if necessary and appropriate leadership skill were displayed), and communication-based metrics. The communication metrics were used to decompose speech into key elements further discussed in Cha et al 2021.…”
Section: Methodsmentioning
confidence: 99%
“…Measuring NTS to improve patient safety has traditionally been done through trained raters’ behavior-based rating tools. In general, NTS assessment tools are checklist-based, time- consuming, and require trained raters to complete (Cha et al, 2021; Yule et al, 2006). Although objective metrics utilizing sensor-bases measures of various NTS constructs were found in a recent scoping review, it was found that none exist to measure leadership skills (Cha & Yu, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Non-technical skills (NTS) have recently been developed to improve surgical team performance. They are currently being developed for high-quality surgical procedures and applied in robotic surgery [ 2 , 3 ]. NTS is defined as “cognitive, social, and personal resource skills that complement technical skills and contribute to safe and efficient task performance.” [ 4 ] NTS includes several concepts of cognitive, social, and personal skills, such as situational awareness, decision-making, communication and teamwork, and leadership.…”
Section: Introductionmentioning
confidence: 99%
“…Non-technical skills (NTS) have recently been developed to improve surgical team performance. They are currently being developed for high-quality surgical procedures and applied in robotic surgery [2,3]. NTS is defined as "cognitive, social, and personal resource skills that complement technical skills and contribute to safe and efficient task performance."…”
Section: Introductionmentioning
confidence: 99%